Size dependence of the surface spin disorder and surface anisotropy constant in ferrite nanoparticles - Gerina, Marianna; Sanna Angotzi, Marco; Mameli, Valentina; Gajdošová, Veronika; Rainer, Daniel N; Dopita, Milan; Steinke, Nina-Juliane; Aurélio, David; Vejpravová, Jana; Zákutná, Dominika (Nanoscale advances, 2023)
The magnetic properties of nanoscale magnets are greatly influenced by surface anisotropy. So far, its quantification is based on the examination of the blocking temperature shift within a series of nanoparticles of varying sizes. In this scenario, the surface anisotropy is assumed to be a particle size-independent quantity. However, there is no solid experimental proof to support this simplified picture. On the contrary, our work unravels the size-dependent magnetic morphology and surface anisotropy in highly uniform magnetic nanoparticles using small-angle polarized neutron scattering. We observed that the surface anisotropy constant does not depend on the nanoparticle's size in the range of 3-9 nm. Furthermore, our results demonstrate that the surface spins are less prone to polarization with increasing nanoparticle size. Our study thus proves the size dependence of the surface spin disorder and the surface anisotropy constant in fine nanomagnets. These findings open new routes in materials based on a controlled surface spin disorder, which is essential for future applications of nanomagnets in biomedicine and magnonics.